Restructuring Conceptual Understanding: The Efficacy of Representation-Based Remedial Learning on Algebraic Misconceptions - Dinda Aulia; Usman Agani; Cut Morina Zubainur; Arhamni Hamid (Jurnal Pendidikan Progresif, 2026)
Misconceptions remain a major problem in mathematics learning at the junior high school level, particularly in algebraic expressions, which require conceptual understanding and the ability to translate various mathematical representations. This study aims to assess improvements in students' conceptual understanding and analyze changes in the types of misconceptions following the implementation of mathematical representation-based remedial learning. This study used a mixed methods approach with an explanatory sequential design. The subjects comprised 33 eighth-grade students at a public junior high school in Banda Aceh City, Indonesia, selected using purposive sampling. Quantitative data were collected using a three-tier diagnostic test before and after the intervention. In contrast, qualitative data were obtained through semi-structured interviews to deepen and contextualize the quantitative findings. Quantitative analysis was conducted using nonparametric statistics, while qualitative data were analyzed through the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the analysis showed a statistically significant increase in students' conceptual understanding, with normalized gain values in the moderate category. Qualitative findings showed a decrease in misconceptions regarding interpreting algebraic symbols and translating problem language into mathematical models, as well as a shift in the structure of students' understanding when interpreting relationships among representations. However, misconceptions stemming from weaknesses in prerequisite concepts, particularly integer operations, tended to persist after the intervention. Furthermore, the increase in correct answers accompanied by low confidence levels suggests that some students' understanding remains traditional and not yet fully stable. Overall, the results of this study indicate that remedial learning based on mathematical representations is associated with improved conceptual understanding and shifts in certain patterns of misconceptions, and provide practical implications for developing learning strategies that are more adaptive to students' conceptual characteristics. Keywords: algebraic expressions, conceptual understanding, misconceptions, remedial teaching, mathematical representation.